Bilateral Radiation Optic Neuropathy Following Concurrent Chemotherapy and Radiation in Glioblastoma. (3rd September 2017) - Thakkar, Jigisha P.; Slevin, John T.; Smith, Charles D.; Sudhakar, Padmaja; St. Clair, William; Villano, John L.
ABSTRACT: Radiation optic neuropathy (RON) is an iatrogenic complication that causes severe, irreversible vision loss within months to years following radiation to lesions close to the visual pathway. The authors describe a case of RON in glioblastoma after radio-sensitisation with temozolomide with sequential involvement of both optic nerves. This case provides a timeline for clinical and imaging findings with RON and specifically resolution of nerve enhancement. The authors also highlight the potential of an increase in incidence of RON in glioblastoma with advances in survival seen with greater use of second-line chemotherapy and even re-radiation.